Examining the Nexus between Nature, Wealth and Power in the Lake George Fishery: The Case of Major Actors in the Fish Product Chain - Keizire, Boaz Blackie; Muhwezi, Wilson Winstons; Natuhwera, Carolyn; Kayiso, Fulgencio (Advocates Coalition for Development and Environment ACODE, 2006)
Lake George is an important fish habitat that supports fish stocks estimated to be worth 4-5 billion shillings per year. Secondly, the economic value of fish to the Ugandan economy reached record levels in 2005 with fish exports reaching US $143 million. Fishing is being viewed as a potential growth sub-sector with potential to contribute significantly to national GDP and ensure eradication of poverty. Fishing also has other multiplier benefits of boosting other sectors of the economy like construction (buildings at most landing sites), manufacturing (foods and beverages e.g. beer, sodas, spirits, wines etc), and the transport. From our research, emerging evidence point to the fact that overemphasis on fish conservation without corresponding emphasis on power (governance), economic relations and behavioral patterns found among the actors largely account for the marginal successes in poverty eradication based planning that has been emphasized for a while.